2017
DOI: 10.1016/j.ydbio.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The spinal cord shows the way – How axons navigate intermediate targets

Abstract: Functional neural circuits depend on the establishment of specific connections between neurons and their target cells. To this end, many axons have to travel long distances to reach their target cells during development. Studies addressing the molecular mechanisms of axon guidance have to overcome the complexity of subpopulation-specific requirements with respect to pathways, guidance cues, and target recognition. Compared to the brain, the relatively simple structure of the spinal cord provides an advantage f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 96 publications
0
31
0
Order By: Relevance
“…A puzzling question of commissural axon navigation across the FP relates to the mode of action by which FP cues exert their effect. Proper FP crossing is thought to rely on a balance of positive and negative forces that support growth cone attachment, motility and direction (de Ramon Francàs et al, 2017). Early experiments conducted in the chicken embryo demonstrated that contacts engaging various Ig Superfamily Cell Adhesion Molecules expressed by growth cones and glia cells control the entry in the FP (Stoeckli et al, 1997;Fitzli et al, 2000).…”
Section: Commissural Axon Navigation Is Driven By Restriction Of Growmentioning
confidence: 99%
“…A puzzling question of commissural axon navigation across the FP relates to the mode of action by which FP cues exert their effect. Proper FP crossing is thought to rely on a balance of positive and negative forces that support growth cone attachment, motility and direction (de Ramon Francàs et al, 2017). Early experiments conducted in the chicken embryo demonstrated that contacts engaging various Ig Superfamily Cell Adhesion Molecules expressed by growth cones and glia cells control the entry in the FP (Stoeckli et al, 1997;Fitzli et al, 2000).…”
Section: Commissural Axon Navigation Is Driven By Restriction Of Growmentioning
confidence: 99%
“…How axons are wired up in an organism is an open and interesting question. In the spinal cord, axons specified as ipsilateral are found on either side of the midline (ipsilateral, contralateral), whereas the commissural axons cross the midline and connect the two body halves (de Ramon Francàs et al, 2017;Sakai and Kaprielian, 2012; Graphical Abstract in the Appendix). The midline separates the right and left body halves and represents a crucial guidance point for the growing axons.…”
Section: Introductionmentioning
confidence: 99%
“…The midline separates the right and left body halves and represents a crucial guidance point for the growing axons. Errors of midline guidance can have deleterious effects on further development of the organism (Comer et al, 2019(Comer et al, , 2015de Ramon Francàs et al, 2017;Tessier-Lavigne and Goodman, 1996). In light hereof, it is not surprising that many of the known axonal guidance receptorligand pairs have been characterized in conjunction with studies of axons crossing the midline; including the classical four sets of receptor-ligand molecules: Robos-Slits, DCCs-Netrins, Plexins-Semaphorins and Ephs-Ephrins (Chédotal, 2019;de Ramon Francàs et al, 2017;Kolodkin and Tessier-Lavigne, 2011;Stoeckli, 2018;Tessier-Lavigne and Goodman, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Again, we have little understanding of this interaction, but the observations of the effects of monocular enucleation are suggestive of a change in cell surface protein expression on the crossing fibres as they move through the midline domain. Such changes in cell surface proteins at the midline have been shown in spinal anterolateral projections as they decussate (Dodd et al ., ; reviewed in de Ramon Francàs et al ., ).…”
mentioning
confidence: 99%